Activity of Scorpion Venom-Derived Antifungal Peptides against Planktonic Cells of Candida spp. and Cryptococcus neoformans and Candida albicans Biofilms - Guilhelmelli, Fernanda; Vilela, Nathália; Smidt, Karina S.; de Oliveira, Marco A.; da Cunha Morales Álvares, Alice; Rigonatto, Maria C. L.; da Silva Costa, Pedro H.; Tavares, Aldo H.; Freitas, Sônia M. de; Nicola, André M.; Franco, Octávio L.; Derengowski, Lorena da Silveira; et al. (Frontiers in Microbiology, 2016)
The incidence of fungal infections has been increasing in the last decades, while the number of available antifungal classes remains the same. The natural and acquired resistance of some fungal species to available therapies, associated with the high toxicity of these drugs on the present scenario and makes an imperative of the search for new, more efficient and less toxic therapeutic choices. Antimicrobial peptides (AMPs) are a potential class of antimicrobial drugs consisting of evolutionarily conserved multifunctional molecules with both microbicidal and immunomodulatory properties being part of the innate immune response of diverse organisms. In this study, we evaluated 11 scorpion-venom derived non-disulfide-bridged peptides against Cryptococcus neoformans and Candida spp, which are important human pathogens. Seven of them, including two novel molecules, showed activity against both genera with MICs values ranging from 3.12 to 200 µM and an analogous activity against C. albicans biofilms. Most of the peptides presented low hemolytic and cytotoxic activity against mammalian cells. Modifications in the primary peptide sequence, as revealed by in silico and circular dichroism analyses of the most promising peptides, underscored the importance of cationicity for their antimicrobial activity as well the amphipathicity of these molecules and their tendency to form alpha helices. This is the first report of scorpion-derived AMPs against C. neoformans and our results underline the potential of scorpion venom as a source of antimicrobials. Further characterization of their mechanism of action, followed by molecular optimization to decrease their citotoxicity and increase antimicrobial activity, is needed to fully clarify their real potential as antifungals.